ANALISIS KERUSAKAN JALAN DESA MEKARSARI KABUPATEN LOMBOK BARAT PROVINSI NUSA TENGGARA BARAT: Analysis Of Road Damage In Mekarsari Village, West Lombok Regency, West Nusa Tenggara Province - Gollu, Albina Alfrida; Aminullah, Aminullah; Dharma S., Bagus Widhi (Yayasan Al-Amin Qalbu, 2025)
The purpose of this study was to determine the dominant type of damage occurring on roads in Mekarsari Village and to determine the condition rating for each road segment studied. This research is a case study of road damage in Mekarsari Village. This study was conducted in the Mekarsari Village area, selecting a 3-km road segment with a width of >4 meters, located in the Mekarsari area of ​​West Lombok Regency. The results showed that the 3-km road segment studied in Mekarsari Village had a total damage volume of 106 m3, consisting of several types of damage: cracks (61 m2), pavement (9 m2), subsidence (3 m3), thickness (8 m3), and grooves (25 m). Therefore, the dominant type of damage was cracks (61 m2). The condition rating for the road segment was 6, indicating a condition requiring routine maintenance.